Instrumental music education: teaching with the musical and practical in harmony - Feldman, Evan (Routledge, 2011)
This textbook presents an extensive look at the topics most vital to running a successful instrumental music program, balancing musical, theoretical, and practical approaches. A central theme is the compelling parallel between language and music, including "sound-to-symbol" pedagogies. --from publisher description